2023
DOI: 10.3390/ani13040692
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Black Korean Goat Meat with Various Slaughter Ages

Abstract: This study was conducted to analyze the physicochemical properties of black goat meat according to the slaughter age (3, 6, 9, 12, 24, 36 months). The moisture content tended to decrease, whereas the fat content, pH, and free amino acid composition tended to increase with increasing slaughter age. The collagen content increased significantly with the increasing slaughter age (p < 0.05). The cooking yield showed a tendency to increase up to 12 months of age, and there was no significant difference after 12 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The pH level is a critical factor that influences the extent of protein–water interaction, thereby dictating the magnitude of water loss. (Choi et al ., 2023) conducted a series of experiments on black goat carcasses, wherein they observed that when the pH of the meat reaches the protein isoelectric point, the net protein charge approaches zero. The drop in charge results in a reduction in repulsive forces between protein groups, hence promoting the occurrence of collisions and enhancing the cohesion among protein molecules.…”
Section: Water Loss Of Meat and Meat Productsmentioning
confidence: 99%
“…The pH level is a critical factor that influences the extent of protein–water interaction, thereby dictating the magnitude of water loss. (Choi et al ., 2023) conducted a series of experiments on black goat carcasses, wherein they observed that when the pH of the meat reaches the protein isoelectric point, the net protein charge approaches zero. The drop in charge results in a reduction in repulsive forces between protein groups, hence promoting the occurrence of collisions and enhancing the cohesion among protein molecules.…”
Section: Water Loss Of Meat and Meat Productsmentioning
confidence: 99%